Pengaruh Lingkungan Sosial Terhadap Perkembangan Psikologis Anak Sekolah Dasar - Ranti Satriani Putri; Neviyarni; Zelhendri Zen (CV. Lenggogeni Data Publishing, 2025)
This study aims to examine the influence of the social environment on the psychological development and learning outcomes of elementary school children. The social environment, which includes family, school, and the surrounding community, plays an important role in shaping the emotional, social, and cognitive aspects of children. The results of the study indicate that a positive and supportive social environment can improve children's psychological development, such as self-confidence, motivation, and emotional stability, and contribute to improving learning achievement. Conversely, a less supportive social environment can cause psychological disorders and reduce children's motivation and learning outcomes. These findings emphasize the need for an active role for parents, teachers, and the community in creating a conducive social environment to support the psychological and academic development of elementary school children. This study provides an overview of the importance of collaboration between various parties to improve the quality of education and psychological well-being of children during their growth.